Digital Navigation Improves No-Show Rates and Bowel Preparation Quality for Patients Undergoing Colonoscopy: A Randomized Controlled Quality Improvement Study. Issue 2 (February 2022) - Solonowicz, Olga; Stier, Matthew; Kim, Karen; Kupfer, Sonia; Tapper, Elliot; Sengupta, Neil
Abstract : Objectives: Because of high historical no-show rates and poor bowel preparation quality in our unit, we sought to evaluate whether text message navigation for patients scheduled for colonoscopy would reduce no-show rates and improve bowel preparation quality compared with usual care. Methods: We performed a randomized controlled quality improvement study from April to August 2019 in an urban academic endoscopy unit. All patients scheduled for colonoscopy were randomly assigned to a control group that received usual care (paper instructions/nursing precalls) or to the intervention group that received usual care plus the text message program [short message service (SMS)]. The program provided timed-release instructions on dietary modifications and bowel preparation before colonoscopy. The primary outcome was no-shows. Secondary outcomes were no-show/same-day cancellations, no-show/cancellations within 7 days of the procedure, and bowel preparation quality. Results: A total of 1625 patients were randomized (SMS=833, control=792). No-show rates were significantly lower in the SMS group compared with the control group (8% vs. 14%; P <0.0001). Similar results were found for no-show/same-day cancellations (10% vs. 16%; P =0.0003), and no-show/cancellations within 7 days (18% vs. 26%; P =0.0008). There was no difference in adequate bowel preparation for all colonoscopies between the groups (89% vs. 87%; P =0.47). However, rates of adequate bowel preparation for screening/surveillance colonoscopies were significantly higher in SMS versus control groups (93% vs. 88%; P =0.04). Conclusions: Text message navigation for patients scheduled for colonoscopy improved the quality of colorectal cancer screening by decreasing no-show rates and increasing adequate bowel preparation rates in patients undergoing screening colonoscopy compared with usual care. Abstract : Supplemental Digital Content is available in the text.